2007
DOI: 10.1017/s0029665107005812
|View full text |Cite
|
Sign up to set email alerts
|

One is okay, more is better? Pharmacological aspects and safe limits of nutritional supplements

Abstract: The use of vitamins, minerals and other supplements has increased considerably during recent years. In the National Diet and Nutrition Survey of British adults aged 19-64 years 40 % of those surveyed were taking supplements. In 2005 sales of dietary supplements in the UK were approximately £325 . 7 · 10 6 in 'bricks and mortar' shops (excluding health food shops). The physiological effects of vitamins and minerals in amounts approximating to the UK reference nutrient intake or the EU RDA are well understood in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 105 publications
0
17
0
Order By: Relevance
“…Risk assessment models used to derive tolerable upper intake levels, safe upper levels, or guidance levels for vitamins and minerals have been established by advisory or regulatory authorities in Australia, Europe, New Zealand, United Kingdom, and the USA [134]. As it is unethical and infeasible to conduct clinical trials targeted at adverse outcomes, these values are based on harm observed in animal model studies and/or available case reports of clinical evidence of toxicity.…”
Section: Benefits and Safety Of Dietary Supplementationmentioning
confidence: 99%
“…Risk assessment models used to derive tolerable upper intake levels, safe upper levels, or guidance levels for vitamins and minerals have been established by advisory or regulatory authorities in Australia, Europe, New Zealand, United Kingdom, and the USA [134]. As it is unethical and infeasible to conduct clinical trials targeted at adverse outcomes, these values are based on harm observed in animal model studies and/or available case reports of clinical evidence of toxicity.…”
Section: Benefits and Safety Of Dietary Supplementationmentioning
confidence: 99%
“…Adapted and combined from Refs. (40,83,109) . LRNI, lower reference nutrient intake; EAR, estimated average requirement; RNI, reference nutrient intake; SUL, safe upper level.…”
Section: Supplement Nutrient Intake: Extremes Of the Distributionmentioning
confidence: 99%
“…Safety is the overarching issue in drug development today, but little was done historically to determine if the antioxidant being tested for an inflammatory-mediated cardiovascular manifestation is safely tolerated at the levels required to provide therapeutic relief [71, 72]. Since the high standards of chemistry, manufacturing, and controls (CMC) required for pharmaceutical drugs are unlikely to be applied to nutraceutical or dietary-supplement-type products, many of the questions regarding safety and efficacy of antioxidants will most likely be answered in the future related to the development of proprietary prodrugs seeking regulatory approval.…”
Section: Safety Now An Overarching Issuementioning
confidence: 99%